Certificate Appointing Glenn Seaborg as a Member of the Atomic Energy Commission - United States. Bureau of Engraving and Printing (1970)
Appointment conferred by President Richard Nixon.
Keywords: Seaborg, Glenn T. (Glenn Theodore), 1912-1999; Rogers, William P. (William Pierce), 1913-2001; U.S. Atomic Energy Commission; Nixon, Richard M. (Richard Milhous), 1913-1994; Nobel Prize winners